POTENSI EKSTRAK ETANOL DAUN SUKUN (Artocarpus altilis) SEBAGAI BAHAN TABIR SURYA DENGAN PENENTUAN NILAI Sun Protection Factor (SPF) SECARA In Vitro - Jariah, Ainun; dupppa, muhammad taufiq; Masri, Anshari; Rukman, Wira Yustika; Muhammad Guntur; Andi Budirohmi (Akademi Farmasi Yamasi Makassar, 2025)
This study aims to determine the value of Sun Protection Factor (SPF) In Vitro Leaf Extract Ethanol Breadfruit (Artocarpus altilis) as a Material Sunscreen. The study design was an observational laboratory that carried out in the Laboratory Farmakognosi-fitokimia Study Pharmacy Faculty of Medicine and Health, Muhammadiyah University. In a study determining the SPF in vitro is done by making a solution of ethanol extract of leaves of breadfruit with a concentration of 25 ppm, 50 ppm, 100 ppm and 200 ppm were then the absorbance is measured using a UV-Vis spectrophotometer at a wavelength of 290-320 nm at intervals of 5 nm. The results showed that the ethanol extract of leaves of breadfruit at a concentration of 25 ppm by 1600, 50 ppm at 2.5966, 6.9166 at 100 ppm, and 200 ppm of 50.6811. Based on the results of this study concluded that the ethanol extract of leaves of breadfruit can be used as a sunscreen active ingredient in concentrations above 50 ppm (SPF value> 2).